Design of an E-Learning Course on control systems modeling for students in applied physics. Issue 2 (1st December 2022) - Tugashova, L; Bazhenov, R; Vikhtenko, E; Borodin, I; Alekseeva, L
Abstract: The research aims to prepare an e-learning course on 'Identification and Mathematical Modeling of Control systems' for students in Applied Physics. The software systems Matlab/Simulink, SciLab/Xcos are used for working mastering of the tutorial. The training is based on scaffolding principles, i.e. gradual complication of tasks. The e-learning course is designed in Moodle. It provides easy input and output (import and export) of the course content. The paper presents characteristic properties of the offered course development, which involves many constituent elements and resources of the platform: Page, Glossary, File, Chat, Forum, Presentation, Video lecture, Assignment, Comment, Test, Book, Interactive content, Hyperlink, and Database. The piloting was conducted at Almetyevsk State Oil Institute and Sholom-Aleichem Priamursky State University, Pacific National University, and Far Eastern State Transport University in 2020-2021. The designed online course is introduced in learning based on the distance learning system of Almetyevsk State Oil Institute Digital University. The student's knowledge and skills assessment over the above-mentioned length of studies prove the effectiveness of the electronic learning resource applied for different kinds of learning. The electronic learning resource is turned out to be useful when changing to distance learning and in the blended learning model.